2021
DOI: 10.1371/journal.pone.0252746
|View full text |Cite
|
Sign up to set email alerts
|

School functioning of children with perinatal HIV-infection in high-income countries: A systematic review

Abstract: Introduction Since the introduction of combination antiretroviral therapy, human immunodeficiency virus (HIV) infection is a manageable chronic disease. However, school-age children (4–18 years) living with HIV could still experience problems with functioning at school, due to the impact of the virus itself, medication, comorbidities and social stigma. School functioning covers academic achievement, school attendance, and social relationships and is of utmost importance to optimize normal participation. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
(214 reference statements)
0
3
0
Order By: Relevance
“…Child schooling and visitations, particularly children in boarding schools and those who take long visitations to grandparents' and aunts' places, negatively in uenced the receipt of disclosure of their HIV diagnosis. The negative nding about boarding schools discon rms previous studies in Kenya [47], Brazil [50], and the Western world [51]. Thus, more research is needed to document the school HIV management systems for caring for children living with HIV in this and similar settings.…”
Section: Discussionmentioning
confidence: 91%
“…Child schooling and visitations, particularly children in boarding schools and those who take long visitations to grandparents' and aunts' places, negatively in uenced the receipt of disclosure of their HIV diagnosis. The negative nding about boarding schools discon rms previous studies in Kenya [47], Brazil [50], and the Western world [51]. Thus, more research is needed to document the school HIV management systems for caring for children living with HIV in this and similar settings.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, as Opstal et al suggest that, when discussing the locus of this neuropsychological problem, it is necessary to consider not only HIV infection but also different aspects of socio-economic and cultural factors. 7 The study also demonstrated the possibility of conducting neuropsychological assessments with children infected with HIV through MTCT using age-appropriate neuropsychological tests. Standardized testing tools for infants and children need to be developed to facilitate investigating the long-term neuropsychological prognosis of children infected through MTCT of HIV by comparing them with adults.…”
mentioning
confidence: 86%
“…In addition, considering the potential neuropsychological and psychosocial challenges, it is not surprising that HIV-infected children may have difficulties in school functioning. Studies report on learning problems, drop-outs, the need for extra support at school, and enrollment in fulltime special education [11][12][13]. Education is universally recognized to be essential for children's development; for HIV-infected children, education is specifically important to provide a sense of normalcy and to reduce risk behavior [14].…”
Section: Introductionmentioning
confidence: 99%